2007
DOI: 10.1111/j.1751-553x.2007.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin: a review of the major allele frequencies worldwide and their association with diseases

Abstract: Summary Haptoglobin (Hp) is a plasma α2‐glycoprotein which binds free haemoglobin, thus preventing oxidative damage. The complex is rapidly removed from the circulation by a specific receptor (CD163) found on macrophages. Three major subtypes, Hp1‐1, Hp2‐1 and Hp2‐2 are the product of two closely related genes HP1 and HP2. The frequency of the HP1 and HP2 genes varies worldwide depending on racial origin: the HP1frequency varying from about 0.07 in parts of India to over 0.7 in parts of West Africa and South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
207
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(224 citation statements)
references
References 114 publications
15
207
0
2
Order By: Relevance
“…These phenotypes are correlated to susceptibility to various diseases ranging from heart and infectious diseases to cancer. The HP serum level varies among different phenotypes, since the lowest amount is present in HP 2-2 and the highest in HP 1-1 patients (18). Notably, evidence reveals specific profiles of HP-α chain in sera from breast, ovary and head and neck cancers (15,17,19).…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypes are correlated to susceptibility to various diseases ranging from heart and infectious diseases to cancer. The HP serum level varies among different phenotypes, since the lowest amount is present in HP 2-2 and the highest in HP 1-1 patients (18). Notably, evidence reveals specific profiles of HP-α chain in sera from breast, ovary and head and neck cancers (15,17,19).…”
Section: Discussionmentioning
confidence: 99%
“…None of our top SNPs were analyzed in those studies, but the most significant SNP in the eQTL analyses by Zeller et al (15) is rs6499560, an SNP that is also associated with the peptide levels in our data (P value = 2.92 × 10 −13 ). Haptoglobin is an Alpha-2-glycoprotein that binds free hemoglobin and protects tissues from oxidative damage and has been associated with a large number of disease states, including cardiovascular diseases, diabetes, cancer, and persistence of various infections (17), as well as regulation of serum lipid levels (2,18). Two different polymorphisms in the HP gene have been suggested to play an important role in protein activity.…”
Section: Discussionmentioning
confidence: 99%
“…Because GPx-scavenger of nitric oxide (NO), a free radical vital in basal blood flow regulation and vascular homeostasis, regulating NO bioavailability and vascular homeostasis. [18] Several functional differences reported between Hp phenotypes could have important biological and clinical consequences. These differences are explained by a phenotype-dependent modulation of oxidative stress and prostaglandin synthesis.…”
Section: Wwwantioxorg Discussionmentioning
confidence: 99%
“…Moreover, the ability of the serum glycoprotein haptoglobin (Hp) to block hemoglobininduced oxidative stress and damage is reportedly phenotype dependent. [18] Since the prudent recommendation for physically active individuals is a diet rich in antioxidants from natural foods, [10] natural antioxidant supplementation can prevent exercise-induced damage in athletes who exercise strenuously and exceed their endogenous antioxidant defenses [9] or even for those who were born less genetically favored by the antioxidant defense system. In previous studies, our group demonstrated that carotenoid-rich oil from pequi (Caryocar brasiliense Camb.…”
Section: Introductionmentioning
confidence: 99%